2009
DOI: 10.1292/jvms.71.549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Condition Score of the Dairy Cow on the in vitro Immune Response of Peripheral Blood Mononuclear Cells to Progesterone Stimulation

Abstract: ABSTRACT. Immune function in cows is closely associated with their physical and hormonal conditions. In order to clarify the relationship between the body condition score (BCS) of lactating dairy cows and the immune response to progesterone (P 4 ) in vitro, we examined whether lower BCS in dairy cows affects the responsiveness of peripheral blood mononuclear cells (PBMCs) to P 4 added in to culture medium. Forty-two non-pregnant healthy Holstein dairy cows were examined at 61 to 120 days after calving. The cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This condition happens because in cows deficient in nutrients such as vitamin E and selenium, lymphocytes, and neutrophils will reduce the ability of lymphocytes and neutrophils in cell phagocytosis, cell proliferation, and the ability of the immune response [10]. In the study of Ohtsuka et al [13], it was shown that under low BCS conditions, cows have a higher number of lymphocytes circulating in the body compared to cows with ideal BCS.…”
Section: Discussionmentioning
confidence: 99%
“…This condition happens because in cows deficient in nutrients such as vitamin E and selenium, lymphocytes, and neutrophils will reduce the ability of lymphocytes and neutrophils in cell phagocytosis, cell proliferation, and the ability of the immune response [10]. In the study of Ohtsuka et al [13], it was shown that under low BCS conditions, cows have a higher number of lymphocytes circulating in the body compared to cows with ideal BCS.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant cattle, progesterone levels increase steadily from early to mid-gestation (45). Studies in these animals have shown that progesterone inhibits the expression of pro-inflammatory cytokines INF-c and IL-17 (46,47) but increases the expression of IL-4 (46). In contrast to studies in human and mice, progesterone effects in Treg cells have not been demonstrated (46).…”
Section: The Immune System In the Dammentioning
confidence: 96%
“…In contrast to studies in human and mice, progesterone effects in Treg cells have not been demonstrated (46). As a result, a Th2-biased immunity is a characteristic feature of the pregnant cows (46)(47)(48).…”
Section: The Immune System In the Dammentioning
confidence: 98%